2012
DOI: 10.1371/journal.pone.0034398
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Regulator PerA Influences Biofilm-Associated, Platelet Binding, and Metabolic Gene Expression in Enterococcus faecalis

Abstract: Enterococcus faecalis is an opportunistic pathogen and a leading cause of nosocomial infections, traits facilitated by the ability to quickly acquire and transfer virulence determinants. A 150 kb pathogenicity island (PAI) comprised of genes contributing to virulence is found in many enterococcal isolates and is known to undergo horizontal transfer. We have shown that the PAI-encoded transcriptional regulator PerA contributes to pathogenicity in the mouse peritonitis infection model. In this study, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 85 publications
1
12
1
Order By: Relevance
“…Cryptococcus , Bacillus , and Streptococcus species respond to carbon dioxide to regulate gene expression (4042). The AraC transcriptional regulators RegA in Citrobacter rodentium , PerA in Enterococcus faecalis , and ToxT in Vibrio cholerae directly respond to bicarbonate stimulation (4345). Interestingly, V. cholerae was able to overcome the need for bicarbonate under carbon dioxide-enriched conditions for a ToxT response, but only while shaken (43).…”
Section: Discussionmentioning
confidence: 99%
“…Cryptococcus , Bacillus , and Streptococcus species respond to carbon dioxide to regulate gene expression (4042). The AraC transcriptional regulators RegA in Citrobacter rodentium , PerA in Enterococcus faecalis , and ToxT in Vibrio cholerae directly respond to bicarbonate stimulation (4345). Interestingly, V. cholerae was able to overcome the need for bicarbonate under carbon dioxide-enriched conditions for a ToxT response, but only while shaken (43).…”
Section: Discussionmentioning
confidence: 99%
“…A BLAST search revealed that EbrB had the highest identity (60% AA) with the E. faecalis pathogenicity island encoded regulator, PerA, which is also located adjacent to esp , though downstream located [37]. Recently the regulon of the E. faecalis PerA was studied by comparing the transcriptome of an E. faecalis wild-type strain (E99) with its isogenic perA insertion mutant (DBS01) using microarray and qRT-PCR [37].…”
Section: Discussionmentioning
confidence: 99%
“…Simi-larly, GI genes can be regulated by proteins encoded by the same GI, another GI, or the bacterial host genome, indicating that GIs are well adapted to their hosts. Therefore, GI genes can be regulated by some environmental signals, such as pH (115), osmolarity (116), temperature (117), cell density (118), or the concentration of specific elements (116,(119)(120)(121).…”
Section: Mobile Elementsmentioning
confidence: 99%